An Assessment of Students’ Ability in Disambiguating Grammatical Structures Using Systemic Functional Approach - Santos, Jay Mark B.; Tamco , Albyra Bianca R. Sy (International Journal of Linguistics and Translation Studies, 2020)
The main objective of this study is to assess the students’ ability in disambiguating grammatical structures using Systemic Functional Approach. This study made use of descriptive correlational method of research that utilized a standardized questionnaire as a primary data gathering tool. The respondents of the study were the Education and Communication Arts students from La Consolacion University Philippines. The results were analyzed and interpreted using statistical tests such as frequency, mean, and percentage computation in determining to assess the students’ ability in disambiguating grammatical structures using Systemic Functional Approach. lastly, it is suggested that the notional-functional aspects be incorporated in the language syllabus through the use of functional categories. There are clear benefits associated with the notional-functional syllabus coupled with a communicative teaching approach. A number of implications were drawn based on the findings of the study.